Estudo dos processos de credenciamento de novas instituições de ensino superior e da autorização de novos cursos de graduação presenciais - Salvador, Ricardo Luiz (2010)
This work sets the cornerstone for the historical review of the Evaluation in Higher Education, the 1988 Federal Constitution, which in its article 209 provides that the school is open to private enterprise, provided that met the requirements of national education and subject the "assessment of quality by the public power." He started the process of Evaluation in Higher Education Brazilian. In 1995, federal law 9.131/95, the government created the National Council of Education, for the first time, as tasks of the MEC - Ministry of Education and Culture has made it clear that they should formulate and evaluate the national education politics. Since then, we passed the LDB - Law of Directives and Bases of National Education, federal law 9.394 of December 1996, PAIUB - Institutional Evaluation of Brazilian Universities and ENC - National College Examination, former provão , until we get the regulatory framework Assessment of Higher Education, federal law 10.861 of 14 April 2004, SINAES - National Assessment of Higher Education. On this track historical find over time a number of instruments used by the Ministry of Education to accredit the functioning of new institutions of higher education and allow new undergraduate education. The intention of this study was to analyze only the administrative proceeding for accreditation of institutions of higher education and undergraduate education in face mode, indicating where appropriate, the defects of these processes, their wrongdoings and even their formal constitutions, and therefore, providing technical legal analysis to improve administrative proceeding analyzed